The Post-Disaster Social Dynamics and the Role of Islamic Education for Children in Relocation Areas: A Systematic Literature Review - Abida, Nur Laili; Muttaqin, Ahmad Ihwanul (Journal of Islamic Education Research, 2025)
This study examines the relationship between post-disaster social dynamics and Islamic education for children, focusing on relocation after the Mount Semeru eruption. It explores how shifts in social structure and values affect children’s learning in Taman Pendidikan Al-Qur’an (TPQ), informal institutions that support moral and emotional development. Using a qualitative library research method, the study finds that TPQs play a key role in fostering spiritual resilience, supporting character education, and aiding psychological recovery. The research concludes that Islamic education contributes not only to religious instruction but also to social cohesion and identity formation. Therefore, TPQs should be integrated into post-disaster recovery frameworks, with continuous support from stakeholders to strengthen their role as agents of social transformation. Penelitian ini mengkaji hubungan antara dinamika sosial pasca bencana dan pendidikan Islam anak, khususnya setelah relokasi akibat erupsi Gunung Semeru. Fokusnya pada bagaimana perubahan struktur dan nilai sosial memengaruhi pembelajaran anak di Taman Pendidikan Al-Qur’an (TPQ), lembaga non-formal yang mendukung pembentukan moral dan pemulihan emosional. Melalui metode studi pustaka kualitatif, hasilnya menunjukkan bahwa TPQ berperan penting dalam membangun ketahanan spiritual, mendukung pendidikan karakter, dan membantu pemulihan psikologis. Penelitian menyimpulkan bahwa pendidikan Islam berkontribusi tidak hanya dalam pengajaran agama, tetapi juga dalam memperkuat kohesi sosial dan pembentukan identitas kolektif. Oleh karena itu, TPQ perlu diintegrasikan dalam kerangka pemulihan pasca bencana dengan dukungan berkelanjutan dari para pemangku kepentingan agar tetap berfungsi sebagai agen transformasi sosial.